Primary tuberculosis of cervix: a rare entity not to be missed - Ajay Halder; Purnima Tiwari; Garima Goel; Julie Hansa John (Barpeta Obstetrics and Gynaecological Society, 2022)
Tuberculosis is a major health concern in South-East Asia region. The prevalence of genital tuberculosis has increased over the past decade in few Asian countries. Detailed history and clinical examination is required to suspect this disease in women of reproductive age group. Among all types of genital tuberculosis, tuberculosis of cervix is relatively rare. Such patients present with varied symptoms including menstrual irregularities, post-coital bleeding and vaginal discharge. However, there have been few case reports in literature mentioning unusual presentation of cervical tuberculosis mimicking carcinoma. We are reporting one similar case of a 33-years-old woman who presented to us with secondary amenorrhea and primary infertility. On clinical examination, cervix was found replaced by friable tissue bleeding on touch, looking like malignant transformation. Diagnosis of cervical tuberculosis could be clinched after tissue biopsy which revealed caseous granuloma on histopathological examination and tubercle bacilli on Ziehl-Neelsen staining. Patient was subsequently started on 6 months antitubercular therapy resulting in resumption of her menses after 3 months. One should have high index of suspicion in order to diagnose tuberculosis of cervix in such cases, especially in high prevalence areas, so that patients can be managed appropriately with antitubercular therapy preventing complications.